Pioneer farming in southeast Europe during the early sixth millennium BC: climate-related adaptations in the exploitation of plants and animals - Ivanova-Bieg, Maria; Ethier, Jonathan (PLOS ONE, 2018)
The Old World farming system arose in the semi-arid Mediterranean environments of southwest Asia. Pioneer farmers settling the interior of the Balkans by the early sixth millennium BC were among the first to introduce southwest Asian-style cultivation and herding into areas with increasingly continental temperate conditions. Previous research has shown that the bioarchaeological assemblages from early farming sites in southeast Europe vary in their proportions of plant and animal taxa, but the relationship between taxonomic variation and climate has remained poorly understood. To uncover associations between multiple species and environmental factors simultaneously, we explored a dataset including altitude, five bioclimatic and 30 bioarchaeological variables (plant and animal taxa) for 57 of the earliest farming sites in southeast Europe using Canonical Correspondence Analysis (CCA). An extension of correspondence analysis, CCA is widely used in applied ecology to answer similar questions of species-environment relationships, but has not been previously applied in prehistoric archaeology to explore taxonomic and climatic variables in conjunction. The analyses reveal that the changes in plant and animal exploitation which occurred with the northward dispersal of farmers, crops and livestock correlate with south-north climate gradients, and emphasize the importance of adaptations in the animal domain for the initial establishment of farming beyond the Mediterranean areas.